Transmissão internacional de efeitos de política fiscal : o caso Brasil e México - Oikawa, Italo (2012)
This work studies the macroeconomic interdependence of fiscal policy between Brazil and Mexico in the period of time from 1995 to 2011. The objective is to analize the transmission of fiscal policy effects to some macroeconomics aggregates, such as output and terms of trade, considering Brazil as the home economy and Mexico as the foreign. Thus, this work develops an empirical application of the theoretical model of macroeconomic interdependence proposed by Corsetti and Pesenti (2001), specifies a Structural VAR (Vector Autoregression) model and Impulse Response analysis. The results indicate that when the Mexican government expenditure is relatively higher than the Brazilian government expenditure, the growth rate of output in the home country is reduced permanently. Moreover, the results showed that raises in Mexican government expenditures relatively higher than the Brazilian government expenditures appreciate the home country's terms of trade in the long run. Then, Mexican fiscal policy shocks are beggar-thy-neighbor in the long run.